2022
DOI: 10.1093/jat/bkac001
|View full text |Cite
|
Sign up to set email alerts
|

Tentative Identification of Etazene (Etodesnitazene) Metabolites in Rat Serum and Urine by Gas Chromatography–Mass Spectrometry and Accurate Mass Liquid Chromatography–Mass Spectrometry

Abstract: 2-Benzylbenzimidazole derivatives comprise a small but forensically significant group of synthetic opioids. In humans, the metabolism of some members of this group is extensive, with little or none of the parent compound remaining. The recent detection of the 2-benzylbenzimidazole derivative, etazene (etodesnitazene), in products seized in Russia required the detection of its metabolites in biofluids for forensic toxicology purposes. Using GC-MS and HRAM LC-MS, eight etazene metabolites were found in the urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…In a recent report on N ‐piperidinyl etonitazene, it was already suggested that some metabolites would undergo glucuronide conjugation, but no actual conjugates were found 14 . The present findings are comparable with results obtained in a recent etazene metabolism study performed in zebrafish 6 and rats 21 . As metabolism of drugs may differ for zebrafish/rats and humans due to species differences in, for example, expression of metabolic enzymes, it is important to confirm this in human samples.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In a recent report on N ‐piperidinyl etonitazene, it was already suggested that some metabolites would undergo glucuronide conjugation, but no actual conjugates were found 14 . The present findings are comparable with results obtained in a recent etazene metabolism study performed in zebrafish 6 and rats 21 . As metabolism of drugs may differ for zebrafish/rats and humans due to species differences in, for example, expression of metabolic enzymes, it is important to confirm this in human samples.…”
Section: Resultssupporting
confidence: 89%
“…However, two less abundant N-oxide metabolites were not detected in the human urine and conversely no phase II metabolites were found in the rat samples. 21 In the zebrafish, only the N-dealkylated metabolite M2 was detected, 6 which in the human urine sample was only present in a small amount. Next to the species difference, time between drug intake and sampling and differences in used analytical techniques should also be considered to explain these (small) discrepancies.…”
Section: Resultsmentioning
confidence: 99%
“…Grigoryev et al [ 18 ] reported eight tentative metabolites (M1–M3) and (M5–M9) of etazene ( Figure 1 ) in rat serum and urine by GC–MS and high-resolution accurate mass (HRAM) LC–MS. They tentatively identified these metabolites as products of N-deethylation, O-deethylation, hydroxylation, or N-oxidation of the benzimidazole moiety or a combination of these reactions.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the downstream metabolic products of SOs, high-performance liquid chromatography (HPLC) with mass spectrometry can be employed due to the technique’s inherent specificity, increased sensitivity, and higher throughput [ 17 ] compared to other methods of chromatography. The first report on etazene metabolites in urine was published in 2022 by Grigoryev et al [ 18 ]. Using gas chromatography–mass spectrometry (GC–MS) and liquid chromatography–mass spectrometry (LC–MS) techniques, eight etazene metabolites were found in rat urine and serum by Grigoryev et al [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation